Phyllanthus Emblica as A Preventive Supplement for Viral Pandemic: From Traditional Use to Clinical Research - Nikita S. Wable; Dr. Sachin B. Somwanshi (Asian Journal of Pharmaceutical Research and Development, 2025)
Phyllanthus emblica Linn., commonly known as Indian gooseberry or Amla, is one of the most valued medicinal plants in traditional Indian medicine systems such as Ayurveda, Unani, and Siddha. It is rich in vitamin C, polyphenols, alkaloids, and tannins, which contribute to its diverse pharmacological properties including antioxidant, immunomodulatory, anti-inflammatory, antiviral, hepatoprotective, cardioprotective, and antidiabetic activities. Recent studies have demonstrated that bioactive compounds such as phyllaemblicin B, phyllaemblinol, and phyllaemblicin G7 exhibit strong binding affinities to key SARS-CoV-2 proteins, suggesting potential therapeutic value in viral infections. Traditional and modern pharmacological evidence highlights Amla efficacy in enhancing immunity and managing disorders like respiratory infections, diabetes, cardiovascular disease, and oxidative stress-related conditions. A randomized controlled clinical trial in COVID-19 patients revealed that adjunct therapy with Amla significantly reduced hospital stay, improved oxygen saturation, and alleviated symptoms such as fever, cough, and shortness of breath, without adverse effects. These findings substantiate its role as a safe and effective preventive supplement during viral pandemics. However, larger multicentric trials and mechanistic studies are needed to validate its clinical efficacy and establish dosage guidelines. This review compiles traditional knowledge, phytochemical composition, pharmacological activities, and clinical research evidence on Phyllanthus emblica to explore its potential as a preventive and therapeutic supplement for viral pandemics.